Evaluation of patient safety culture in community pharmacies in the City of Manila - Ocampo, April Dominique M.​; Parojinog, Ark O.​; Ramales, Ayane Mark Q.​
Unsafe medication practices and errors are leading causes of preventable harm in healthcare systems, adversely affecting patient safety, which is one of the key pillars of healthcare quality. One organizational attribute that influences patient safety is patient safety culture. Pharmacists' interventions have been recognized to increase patient safety by detecting medication errors. This study aims to evaluate the perceived patient safety culture of pharmacy personnel in community pharmacies in the City of Manila. The study adapted a self-administered questionnaire from the Agency for Healthcare Research and Quality (AHRQ) which was handed out to the pharmacy staff working in community pharmacies in the City of Manila. Using the Pharmacy Excel version 1.2 tool provided by the AHRQ, ?Patient Counseling? and ?Communication About Mistakes? were concluded as the composites with the highest percent positive score (93%), while ?Staff, Working Pressure, and Pace? had the lowest percent positive score (55%). Moreover, pharmacy personnel in community pharmacies in the City of Manila generally had a positive perception of patient safety culture being observed in their respective work settings.